Don't answer [videorecording (DVD)] - Burd, Howard; Storm, Annabel; Amsler, Jack; Bankert, Adrienne (Indican Pictures, 2025)
Jack Nelson isn't your average delivery driver. When a glitch in the system sets this deeply disturbed man loose with a new job and a pocket full of pills in small-town California, this town full of eccentric locals are in for a nightmare. Each stop on his route exposes a darker truth: Jack isn't looking to deliver peace of mind he's looking for his next victim.